2013
DOI: 10.1111/joca.12021
|View full text |Cite
|
Sign up to set email alerts
|

Borrowing Capacity and Financial Decisions of Low‐to‐Moderate Income First‐Time Homebuyers

Abstract: This study documents the extent to which first-time homebuyers seeking a mortgage accurately estimate their borrowing capacity and how this is associated with their decisions regarding mortgage debt and the take-up of a free offer of financial coaching. We find that consumers who underestimate their nonmortgage debt (31.5% of the sample) also take out larger mortgages relative to income. Consumers who underestimate or overestimate their total debt as well as their monthly debt payments are more likely to accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…These results stand somewhat in contrast to much of the existing literature on financial education interventions, which have produced mixed results to date, even when assessing programs that aim to develop financial capability by combining financial knowledge as well as access to financial products. Instead, our findings are largely consistent with more recent, albeit descriptive, studies specifically focused on financial coaching that find positive associations between coaching and client outcomes including greater confidence, changes in behaviors such as budgeting and saving, and improvements in credit building (Center for Financial Security ; Collins and O'Rourke ; Moulton et al ; NeighborWorks America ). In addition, the experimental study most similar to ours found that financial coaching increased credit scores by as much as 20 points, although these gains were not consistent across the two sites due to low compliance rates (Theodos et al ).…”
Section: Discussionsupporting
confidence: 90%
“…These results stand somewhat in contrast to much of the existing literature on financial education interventions, which have produced mixed results to date, even when assessing programs that aim to develop financial capability by combining financial knowledge as well as access to financial products. Instead, our findings are largely consistent with more recent, albeit descriptive, studies specifically focused on financial coaching that find positive associations between coaching and client outcomes including greater confidence, changes in behaviors such as budgeting and saving, and improvements in credit building (Center for Financial Security ; Collins and O'Rourke ; Moulton et al ; NeighborWorks America ). In addition, the experimental study most similar to ours found that financial coaching increased credit scores by as much as 20 points, although these gains were not consistent across the two sites due to low compliance rates (Theodos et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Perceived borrowing constraints (hereafter PBC) are of great importance because they lie at the core of innumerous financial decisions. Misperceptions of borrowing constraints lead to suboptimal financial decisions (e.g., Levinger, Benton, and Meier ; Moulton et al ; Perry ), such as the acceptance of less favorable credit terms and overspending. Therefore, it is important to determine what drives such perceptions, so that effective financial education programs can be tailored to improve consumers' financial literacy.…”
mentioning
confidence: 99%
“…Two other recent studies analyze the relationship between financial literacy and the effects of financial advice in the mortgage market. Moulton et al (2013) argue that first-time home-buyers who underestimate or overestimate their total debt or misunderstand monthly debt payments are more likely to seek financial counseling. Agarwal et al (2014) find that financial counseling has no direct effect on mortgage choices, but an indirect effect occurs via mandatory counseling discouraging low credit score borrowers from applying for risky mortgages.…”
Section: Introductionmentioning
confidence: 99%